An Economic Evaluation of Electricity Generation Options in Nigeria - Eziyi, Ijeoma L. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Over the past two decades, electricity prices have been highly subsidized for consumers in Nigeria. Because of this, investment in the power sector has not been competitive, leaving the economy with a capacity deficient power sector. The country loses approximately $13bn yearly on imported captive generating plants used for self-generation. This study aims at analyzing the various power generation options for Nigeria. The evaluation uses an economic cost-benefit analysis approach to estimate the cost of various options that can be explored in Nigeria, and computes the consumers’ willingness to pay for electricity (taking into account the high level of self-generation presently in the country). In this study, taking a series of hypothetical plant capacity as would be required to meet the current shortages; results show that the Nigerian economy could realize a net benefit of $4.9 billion, in present value terms, if the country embarks on hydro power investment as replacement for the current shortages. If solar PV is chosen, the economy could realize a net benefit of $21.1 billion in present value terms. If open cycle gas as replacement, the economy could benefit a net present value of $25.6 billion, and if the country goes for combined cycle gas plant, the economy could benefit $29.3 billion in net present value terms. These results are sensitized for different prices of fuel over the period of analysis covered in this study. Therefore, there is strong evidence that the country stands to benefit from any amount of electricity supplied through the national grid as a replacement for the self-generation. Keywords: Power Generation, Nigeria, Economic Analysis

ÖZ : Nijerya’da tüketicilere sunulan elektrik enerjisi tüketim bedelleri özelikkle son yirmi yılda oldukça sübvanse edilmiştir. Bunun sonucu olarak elektrik enerjisi piyasası rekabetçi olmayan bir yapıya bürünmüştür. Bu da ülke ekonomisinde ciddi bir elektrik enerjisi açığı yaratmaktadır. Bu açığı giderme çabaları sonucu ithal mobil üretim alternatiflerinin Nijerya ekonomisine maliyeti ise yıllık 13 milyar dolar civarındadır. Bu çalışmanın amacı Nijerya için çeşitli elektrik enerjisi üretim alternatiflerini araştırmak ve analiz etmektir. Değerlendirme için ekonomik fayda-maliyet analizi yaklaşımı kullanılarak çeşitli elektrik enerjisi üretim alternatiflerinin maliyetleri Nijerya için hesaplanmıştır. Aynı zamanda tüketicilerin mevcut üretim alternatiflerinin maliyetlerini de dikkate alarak, elektrik için ne kadar fiyat ödemeye meyilli oldukları da hesaplanmıştır. Bu çalışmada, mevcut elektrik kıtlıklarını gidermek için bir dizi hipotetik santral kapasitesine ihtiyaç duyulduğu dikkate alınmıştır. Çalışma bulguları Nijerya’nın hidroelektrik santrallerle bu açığı gidermesi durumunda 4,9 milyar dolar kâr edeceğini ortaya koymuştur. Ülkenin güneş enerjisini mevcut durumda alternatif çözüm olarak ele alması durumunda 21,1 milyar dolar kâr edeceği hesaplanmıştır. Nijerya açık çevrim gaz tesislerini kıtlığı gidermek amacıyla kullanırsa 25,6 milyar dolar, kombine çevrim gaz santrallerini kullanırsa 29,3 milyar dolar kâr edecektir. Çalışma bulguları elde edilirken çalışma için dikkate alınan yıllardaki yakıt fiyatları da hesaba katılmıştır. Bu yüzden çalışmadaki alternatif yöntemlerden herhangi birisini kullanarak elektrik enerjisi üretmek Nijerya için büyük bir avantaj olacaktır. Anahtar kelimeler: Enerji Üretimi, Nijerya, Ekonomik Analiz
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2014. Supervisor: Assist. Prof. Dr. Kamil Sertoğlu.
Keywords: Economics; Economic Conditions - Nigeria; Electric power production - Economics - Nigeria; Power Generation; Nigeria; Economic Analysis